2011
DOI: 10.1016/j.jnoncrysol.2010.05.091
|View full text |Cite
|
Sign up to set email alerts
|

Physical aging in PMMA/silica nanocomposites: Enthalpy and dielectric relaxation

Abstract: We have investigated the physical aging below the glass transition temperature, namely the slow evolution occurring in non-equilibrium glasses, of poly(methyl methacrylate)/silica (PMMA/silica) nanocomposites. To do so we have followed the time evolution of the enthalpy and that of the dielectric strength of PMMA β process during isothermal annealing. The results indicate that physical aging is generally accelerated in all nanocomposites in comparison to pure PMMA, despite the lack of effect of the nanoparticl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 29 publications
2
24
0
Order By: Relevance
“…The constant T g of the PS matrix was attributed to a neutral interface with no attractive interactions between polymer and the NP. This is in contrast to strong interactions, which increase T g or repulsive interfaces which decrease T g . Herein, the phenyltrimethoxysilane functionalization of the silica terminates the hydrophilic hydroxyl‐rich silica surface with phenyl groups, and likely produces a neutral surface to PS.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The constant T g of the PS matrix was attributed to a neutral interface with no attractive interactions between polymer and the NP. This is in contrast to strong interactions, which increase T g or repulsive interfaces which decrease T g . Herein, the phenyltrimethoxysilane functionalization of the silica terminates the hydrophilic hydroxyl‐rich silica surface with phenyl groups, and likely produces a neutral surface to PS.…”
Section: Resultsmentioning
confidence: 90%
“…Even in the glass state where segmental relaxation is localized; such factors impact the evolution of the molecular structure toward its ideal melt‐extrapolated state. For example, nanofillers have been shown to alter physical aging, as well as T g , ranging from no effect, to either an increase or decrease depending on the interactions between the polymer and NPs . These observations are generally consistent with the thin film perspective that interface interactions (repulsive or attractive) alter local mobility of segments relative to regions far from the interface, manifesting in a shift (increase or decrease) of the effective bulk glass transition temperature and physical aging rates .…”
Section: Introductionmentioning
confidence: 75%
“…Fillers are known to affect the physical aging behavior of the host polymer. Boucher et al showed that the addition of surface‐functionalized silica and gold particles accelerated physical aging of poly (methyl methacrylate) (PMMA) and poly(styrene) (PS), respectively . They showed that functionalization did not alter the molecular mechanism for physical aging, but increased the surface‐to‐volume ratio accelerated physical aging.…”
Section: Introductionmentioning
confidence: 98%
“…Available theories [8][9][10] and a number of observations 11, 12 mainly focus on the local nature of physical aging, but do not provide any explanation on the acceleration of physical aging recently encountered in thin films [13][14][15][16][17][18][19] and nanocomposites [20][21][22][23] when the typical size of the system (the thickness in thin films and the interparticle distance in nanocomposites) is of the order of (or lower) than several micrometers. In particular, Boucher et al 20,22 -monitoring the evolution of the dielectric strength of PMMA secondary relaxation 20 and the enthalpy recovery 22 occurring during physical aging of poly(methylmethacrylate) (PMMA) in nanocomposites with silica particles displaying a diameter of the order of several hundreds of nanometers-observed a) Electronic mail: swxcacad@sw.ehu.es.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] To do so, we have solved numerically the second equation of Fick with a free volume dependent diffusion coefficient. [21][22][23] To do so, we have solved numerically the second equation of Fick with a free volume dependent diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%